2015
DOI: 10.1152/ajpregu.00059.2015
|View full text |Cite
|
Sign up to set email alerts
|

To explain the variation of OGTT dynamics by biological mechanisms: a novel approach based on principal components analysis in women with history of GDM

Abstract: Early reexamination of carbohydrate metabolism via an oral glucose tolerance test (OGTT) is recommended after pregnancy with gestational diabetes (GDM). In this report, we aimed to assess the dominant patterns of dynamic OGTT measurements and subsequently explain them by meanings of the underlying pathophysiological processes. Principal components analysis (PCA), a statistical procedure that aims to reduce the dimensionality of multiple interrelated measures to a set of linearly uncorrelated variables (the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
(33 reference statements)
2
11
0
Order By: Relevance
“…This study is aimed at assessing the performance of PCAderived novel indices of glucose metabolism during pregnancy, which were previously developed in postpartum women with history of GDM, in terms of the extent of their correlation with traditional fasting and dynamic parameters of insulin resistance and secretion obtained from OGTT data. Thereby, three PCS were calculated by using the eigenvectors as described in our previous publication [4]. The results showed that all three indices PCS1 to 3 behaved similarly as compared to our previous study in postpartum women [4]: PCS1 showed close associations with various indices of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This study is aimed at assessing the performance of PCAderived novel indices of glucose metabolism during pregnancy, which were previously developed in postpartum women with history of GDM, in terms of the extent of their correlation with traditional fasting and dynamic parameters of insulin resistance and secretion obtained from OGTT data. Thereby, three PCS were calculated by using the eigenvectors as described in our previous publication [4]. The results showed that all three indices PCS1 to 3 behaved similarly as compared to our previous study in postpartum women [4]: PCS1 showed close associations with various indices of insulin sensitivity.…”
Section: Discussionsupporting
confidence: 58%
“…Thereby, three PCS were calculated by using the eigenvectors as described in our previous publication [4]. The results showed that all three indices PCS1 to 3 behaved similarly as compared to our previous study in postpartum women [4]: PCS1 showed close associations with various indices of insulin sensitivity. Moreover, it was inversely related to parameters of insulin secretion suggesting that it also embodies the adaptation to impaired insulin action, which physiologically occurs in normal glucose-tolerant individuals.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Hence, the motivation of our simulation scenarios was rather to give some examples and our simulation scenarios are motivated (and restricted) by the key questions raised by our real data example due to correlated covariables. Moreover, it has to be mentioned, that there might be other methods, which might be used to deal with these problems like orthogonal transformation by (sparse) principal components analysis, which we have recently proposed for the analysis of OGTT data in another report [ 32 ].…”
Section: Discussionmentioning
confidence: 99%